Analysis of the Impact of PPE Implementation on Occupational Safety and Health on Construction(Case Study: 4-Storey Residential Building Project) - Bustamin, Maulidya; Wisnu Abiarto Nugroho; Dwi Sekar Anggraini (Universitas Negeri Semarang, 2025)
Project construction can be risky for workers if Personal Protective Equipment (PPE) is improper and correctly used. Complex construction projects are typically carried out in large cities like Surabaya. Usually, these projects involve contract workers with varying knowledge and awareness regarding PPE use. This study aims to analyze the level of work accident risk in a four-story house project undertaken by PT. Surya Andalan Bina Perkasa in Surabaya. The research method used was quantitative, with data collection techniques using questionnaires distributed to 30 samples. Data analysis techniques were carried out using simple linear regression and hypothesis testing. The study results show the risk level of work accidents in the four-story residential project carried out by PT. Surya Andalan Bina Perkasa is quite low. Types of work accidents with low risk include shortness of breath due to dust, head impacts, injuries from falls from heights, muscle and bone injuries caused by falling materials, hearing loss due to noise, and electric shocks. Types of risks in the low-medium category include irritation due to dust or wood shavings, minor foot injuries, hand injuries, body parts being struck by sharp objects, and accidents caused by heavy equipment. The level of worker compliance with PPE use is still low, as evidenced by 70% of workers being non-compliant and 30% being somewhat compliant in using PPE while working. The study results also show an impact of PPE implementation on occupational health and safety, evidenced by a correlation value of 24.9%. The significance of the hypothesis test is 0.005, and the determination value is 25.3%, indicating that the impact of PPE implementation on occupational health and safety is insignificant, as it only increases occupational health and safety by 25.3%.